Toward the dehumanization of Islamic Education teachers: A conceptual synthesis of workload complexity in the Merdeka Curriculum - Eva Kumalasari; Nayla Wirdatun Ni’ammah; Imam Junaris (PT Bina Perfidia Akademia, 2026)
The implementation of the Merdeka Curriculum has increased teachers' workload through expanding administrative demands, yet previous studies have examined teacher workload, role strain, and dehumanization separately, leaving the underlying mechanism, particularly for Islamic Education (PAI) teachers, insufficiently explained. This study aims to analyze the mechanism of PAI teachers' dehumanization by examining the relationship between educational regulations, the implementation of the Merdeka Curriculum, the professional characteristics of PAI teachers, and the resulting professional consequences. This study employed a library research approach using a conceptual synthesis method based on educational regulations, policy documents, and relevant scholarly literature. The findings reveal that the dehumanization of PAI teachers is not merely a consequence of increasing administrative responsibilities but results from the interaction among expanding regulations, transformed professional responsibilities, and the multidimensional pedagogical, moral, and spiritual roles of PAI teachers. This study contributes a conceptual model explaining the mechanism of teacher dehumanization as a foundation for developing a more humanistic implementation of the Merdeka Curriculum. Abstrak Implementasi Kurikulum Merdeka meningkatkan kompleksitas beban kerja guru melalui perluasan tuntutan administratif, namun kajian sebelumnya masih membahas beban kerja, konflik peran, dan dehumanisasi guru secara terpisah sehingga mekanisme hubungan antarfenomena tersebut, khususnya pada guru Pendidikan Agama Islam (PAI), belum dijelaskan secara komprehensif. Penelitian ini bertujuan menganalisis mekanisme dehumanisasi guru PAI melalui hubungan antara regulasi pendidikan, implementasi Kurikulum Merdeka, karakteristik profesi guru, dan konsekuensi profesional yang ditimbulkannya. Penelitian menggunakan pendekatan library research dengan metode sintesis konseptual melalui analisis regulasi, dokumen kebijakan, dan literatur ilmiah yang relevan. Hasil penelitian menunjukkan bahwa dehumanisasi guru PAI bukan semata-mata disebabkan oleh meningkatnya administrasi pembelajaran, tetapi merupakan konsekuensi dari interaksi antara perluasan regulasi, transformasi pekerjaan guru, dan kompleksitas peran pedagogis, moral, serta spiritual. Penelitian ini berkontribusi dengan menawarkan model konseptual yang menjelaskan mekanisme dehumanisasi guru PAI sebagai dasar evaluasi implementasi Kurikulum Merdeka yang lebih humanis.